Sustainable Learning and Education - Shweta Singh (International Journal of Sustainability, 2024)
Sustainable learning asnd education are approaches to learning that prioritize environmental stewardship, social equity, and economic prosperity. A comprehensive approach to education, sustainable learning and education acknowledges the interdependence of social, economic, and environmental systems. Rather than treating these aspects in isolation, sustainable education integrates them to foster a comprehensive understanding of sustainability issues. Sustainable education places a strong emphasis on systems thinking, which entails comprehending the feedback loops and interactions between various complex system components. By adopting a systems perspective, learners can analyse the root causes of sustainability challenges and identify leverage points for effective intervention. The UNESCO-led program Education for Sustainable Development (ESD) works to advance sustainable education and learning around the globe. By highlighting the importance of education in accomplishing the Sustainable Development Goals (SDGs), ESD seeks to provide students with the information, abilities, values, and attitudes they need to help create a more sustainbleaso in this way this research paper embracing these principles and practices. sustainable learning and education can play a crucial role in empowering individuals, communities, and societies to build a more sustainable and resilient world for present and future generations.
Keywords: Intervention; Sustainability; holistic; skills; sustainable